Isotherm Prediction Of Various Adsorbents On Moisture Removal From Ambient Air By Solver Function - Ariffabilah, Muhammad Ilyasa Saffiq (Universiti Teknologi PETRONAS, 2016)
This report discusses on the research done, work completed of the topic, which is Performance Analysis of Various Adsorbents on Moisture Removal from Ambient Air. This project is collaboration between Universiti Teknologi PETRONAS (UTP) and Gas Processing Kertih (GPK) supervised by Dr. Rashid Shamsuddin and Miss Nurul Aini binti Ahmad Rani, which she is Planner Engineer as well as my host company supervisor during my internship period from 17th May 2015 until 24th December 2015. In this project, the instrument air dryer at GPK face a problem with dew point fluctuating during April 2015, which Dr Rashid come to bring the idea of performing the various adsorbents analysis to which they perform the adsorption of moisture to supply to instrument equipment. In this study, some of adsorbents have been decided which are activated alumina, zeolite, and silica gel as well as an additional new adsorbent which is zeocarbon. The adsorption capacity is investigated by using non- linear isotherm model method with solver function.